CORPORATE CULTURE: LEVELS AND VALUES - Tymoshenko, Dmytro; Slyusar, Iryna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article substantiates the expediency corporate culture development based on European values. The role of corporate culture in the development of organizational leadership is generalized and substantiated. The connection of loyalty with the levels of corporate culture and values that are nurtured by the common cultural field is demonstrated. Suggestions for synchronization of all components of corporate culture into a single position are given. Particular attention is paid to the values that ensure effective corporate governance, taking into account the requirements and challenges of today, which allows both to attract and maintain relevant communications with all stakeholders. It is proved that the attraction to this issue is justified by the trends of modern development: the requirements of globalization and innovation. The connection of three levels of loyalty with three levels of corporate culture, their perception by an individual employee is shown. The mechanism of synchronization of all components of corporate culture in the direction of its development is given